Genômica comparativa de Acinetobacter baumannii: pan-resistoma e evolução - Diego Lucas Neres Rodrigues (2021)
Acinetobacter baumannii is a Gram-negative coccobacillus that has acquired a vast resistance gene repertoire against several antimicrobials. This fact led to the prominence of this bacterium in epidemiological outbreaks around the world. The World Health Organization (WHO) groups A. baumannii with other Multi-Drug Resistant (MDR) microorganisms, forming the ESKAPE group of clinical relevance with Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Enterobacter spp. Bacteria of the genus Acinetobacter also represent a significant problem for One Health because they are also capable of causing mastitis in farm animals, severe infections in humans, and sometimes are identified as environmental contaminants. Thus, for the reconstruction of the species' resistance, it was necessary to understand the development of the problem over time. This work aims to compare in silico the genomes of 206 A. baumannii strains to carry out a study of the meta-analysis of the species and characterize it through analysis of pan-genome and evolution Considering the exposed problem and the global amplitude of multidrug resistance and pathogenicity of this microorganism. As an initial stage of this work, a meta-analysis study was developed for the literary prospection of clinical reports of multi-resistant strains of A. baumannii on the NCBI (National Center for Biotechnology Information) and Cochrane platforms. For the comparative studies, the genomic data of A. baumannii was used against the Comprehensive Antibiotic Resistance Database (CARD) for the formation of the species' resistome. Then, the phylogenetic distribution of the species within the genus was analyzed based on housekeeping genes and the phylogenomic reconstruction of the species A. baumannii based on genes and proteins belonging to the central genome. The bacterial strains were separated based on Type Nucleotide Sequence and Average Nucleotide Identity (ANI). Subsequently, the genomic plasticity analysis was performed using the Genomic Island Prediction Software (GIPSy) and the analysis of the total genetic repertoire of the species using the OrthoFinder software. Thus, the main results obtained were: (i) based on Odds Ratio, A. baumannii has about 355% chance of resistance to carbapenem when compared to the chance of other bacteria; (ii) the repertoire of resistance genes of the species is formed by 171 genes; (iii) there is a higher proportion of genes related to resistance against β-lactams in general, aminoglycosides, tetracyclines; (iv) the amount of glycine and polymyxin resistance genes found was lower than that of the other relevant classes against the species, such as β-lactams; (v) the global distribution of A. baumannii strains is homogeneous and has low clonality due to geographic isolation considering the Type Sequences of the species; (vi) the pan-genome of the species is open, having a central genome formed by 1,999 genes, and an accessory genome formed by 12,336 genes. Therefore, it is concluded that the repertoire of resistance genes of the species is vast and complex, in addition to matching the various clinical cases reported, which indicates that its presence is crucial for bacterial resistance and its success as a pathogen. With that, it was possible to summarize the results of different times and better understand the origin of the evolution of the species' resistance. Future analyses can be carried out to compare the results presented here with other equally problematic microorganisms. In addition, it is possible to apply the results found in the pangenomic analysis to search for vaccine candidates and therapeutic targets against A. baumannii infections.